Pengaruh Kualitas Informasi dan Kualitas Layanan Terhadap Manfaat Bersih Melalui Kepuasan Pengguna Layanan pada Badan Kesbangpol Pemkab Solok - Afdisya, Hanifah; Veri, Jhon (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This study aims to determine the influence of information quality and service quality on net benefits through service user satisfaction at the Solok Regency Government Kesbangpol Agency. This study describes each variable in the DeLone and McLean model to find out the extent of the success of the Solok Regency Government's Kesbangpol Agency in providing services. The research method used is a quantitative method. The sample in this study is 45 employees of the Solok Regency Government Kesbangpol Agency. Data were collected using questionnaires and the results were analyzed descriptively quantitatively using the Partial Least Square (PLS) approach. The results of this study show that there is a positive and significant influence of information quality and service quality on the satisfaction of service users at the Solok Regency Government Kesbangpol Agency. There is a positive and significant influence of information quality and service quality on the net benefits of the Solok Regency Government's Kesbangpol Agency. There is a positive and significant influence of service user satisfaction on the net benefits at the Solok Regency Government's Kesbangpol Agency. Service user satisfaction is able to mediate the influence of information quality on the net benefits of the Solok Regency Government's Kesbangpol Agency. Service user satisfaction is able to mediate the influence of service quality on the net benefits of the Solok Regency Government's Kesbangpol Agency.